2007
DOI: 10.1007/s11295-007-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of intra- and inter-specific hybrids of Eucalyptus globulus and E. nitens

Abstract: Intra-specific hybrids within Eucalyptus nitens and E. globulus were compared directly with inter-specific E. nitens × globulus using common parents. Diameter (age 2, 4, 6, 10 years) and Pilodyn (age 6 years) were used as indirect measures of growth and wood density, respectively. Genetic parameters were estimated for all cross types and traits. A direct comparison of the general combining ability with the general hybridising ability was made. Heterosis was estimated for intra-and inter-specific hybrids. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 23 publications
7
51
1
Order By: Relevance
“…Plant material and crossing design First-generation E. globulus full-sib families, derived from a factorial design involving base population parents from King Island trees, randomly selected in native stands (pollen parents) or a seed orchard (seed parents, chosen from different families remaining in a growth-culled progeny trial based on accessibility of flowers for crossing) (Volker et al, 2008), were used to generate second-generation full-sib families with four degrees of inbreeding: f ¼ 0% from outcrosses, f ¼ 12.5% from crosses among half sibs, f ¼ 25% from matings among full sibs and f ¼ 50% from selfing. The base population parents are assumed to be unrelated and non-inbred.…”
Section: Methodsmentioning
confidence: 99%
“…Plant material and crossing design First-generation E. globulus full-sib families, derived from a factorial design involving base population parents from King Island trees, randomly selected in native stands (pollen parents) or a seed orchard (seed parents, chosen from different families remaining in a growth-culled progeny trial based on accessibility of flowers for crossing) (Volker et al, 2008), were used to generate second-generation full-sib families with four degrees of inbreeding: f ¼ 0% from outcrosses, f ¼ 12.5% from crosses among half sibs, f ¼ 25% from matings among full sibs and f ¼ 50% from selfing. The base population parents are assumed to be unrelated and non-inbred.…”
Section: Methodsmentioning
confidence: 99%
“…If this hypothesis is false, then a hybrid breeding strategy such as Reciprocal Recurrent Selection (RRS;COMSTOCK et al, 1949) has obvious advantages (VIGNERON and BOUVET, 2000). Although some authors indicated a poor correlation between GCA and GHA (RETIEF and STANGER, 2009;VOLKER et al, 2008), literature related to this topic is sparse and more information regarding this is needed. For instance, results of the latter studies were based on the performance of seedling populations and not clonal populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an F 1 (intraspecific) inter-provenance cross between E. globulus from King Island and Taranna, a reduced viability has been noted relative to an intra-provenance cross from King Island. However, the Taranna intra-provenance cross also performed poorly (VOLKER, 2002). Although most studies have demonstrated hybrid incompatibility in the F 1 generation, barriers to hybridisation may also extend to further generations (outbreeding depression) as noted by POTTS et al (2000) where a reduced growth and survival of E. globulus by E. nitens affected F 1 and F 2 generations.…”
Section: Segregation Distortionmentioning
confidence: 98%